Nudging University Students' Achievement Using Best Practice Approach - Bednářová, Ivana; Cingl, Lubomír, 1984-; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
This bachelor’s thesis deals with the behavioural economics theory of nudging and the possibilities of its use in education. The nudge concept is first analysed and discussed from a theoretical point of view, then its specific application is proposed. In a field experiment, a randomly selected group of students from the Prague University of Economics and Business were sent a nudge e-mail encouraging them to increase their study activity through information about the best practice. However, the results of the experiment did not show any significant effect of the measure presented here on the students’ performance and efforts; a slightly negative impact of the nudge was indicated by the score obtained in the midterm test. The work provides findings which can be used in creating policies that contribute to reducing the dropout rates at universities.
Vedoucí práce: Lubomír Cingl
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses